Bilinmeyen Bir 15. Yüzyıl Şairi Serâyî - (:unkn) unknown (My University, 2017)
There has been considerable development in the study and evaluation of literary works in the field of Classical Turkish Literature. But with each passing day, the discovery of previously unknown poets and their poems contribute new information to the already available accumulated knowledge. Serâyî is a poet of the Bayezid II period. This period is regarded as a “transitional period” in which the Divan poem earned its classical identity in the 16th century. The texts of the century authored by poets Şeyhî, Ahmet Paşa and Necatî make it possible for us to conceive this period better – the ones that were registered by the authenthic authors in particular – are valuable on their own besides being valuable because of how rare they are compared to the next century. In this article, having mentioned the general characteristics of the Divan poetry during which the poet lived, information about Serâyî’s life obtained from his works is presented. Using the Vienna National Library Mixt. 1446 records, the Divan of the poet is introduced. Based on his canon, Serâyî’s couplets on poetry and poems, his language and style is exemplified, as well as his similarities with the other poets of his period.

Eski Türk edebiyatı alanında yapılan bilimsel çalışmaların temelini oluşturan edebî eserlerin (konumuz gereği divanların) tespit ve neşrinde günümüzde önemli mesafeler alınmıştır. Ancak, her geçen gün kaynaklarda yer almamış şairlerin ve dolayısıyla eserlerinin ortaya çıkarılması alandaki mevcut birikime yeni katkılar sağlamaktadır. Serâyî, II. Bayezid Dönemi şairlerindendir. Bu dönem, 16. yüzyılda klasik hüviyetini kazandığı kabul edilen divan şiirini hazırlaması açısından bir “geçiş dönemi” olarak kabul edilir. Yüzyılın Şeyhî, Ahmet Paşa ve Necâtî gibi büyük şairlerinin eserleri öncülüğünde böyle bir dönemi daha iyi anlamayı sağlayacak metinler -özellikle müellifinin elinden çıkmış olanlar- kendi başına sahip oldukları değerin yanında sonraki yüzyıllara göre eldeki eser sayısı bakımından daha nadir olmaları dolayısıyla da kıymetlidir. Bu makalede, şairin yaşadığı dönemin divan şiiri açısından genel özellikleri kısaca belirtildikten sonra Serâyî’nin hayatına dair bilgiler divanından elde edilen verilerle ortaya konmuştur. Viyana Millî Kütüphanesi Mixt. 1446 numarada kayıtlı müellif hattı divan tanıtımının ardından yine eserden hareketle Serâyî’nin şiiri/şairliğine dair beyitleri, dil ve üslup özellikleri, dönem şairleriyle olan benzerlikleri örneklendirilmeye çalışılmıştır.
Keywords: Serayi; Şeyhi; Ahmet Paşa; Necati; Divan Edebiyatı; Divan Şiiri; 15. yüzyıl; II. Beyazid; Divan literature; 15th century